Protective role of vitamin D receptor against mitochondrial calcium overload from PM2.5-Induced injury in renal tubular cells - Mengqiu Lu; Zishun Zhan; Dan Li; Hengbing Chen; Aimei Li; Jing Hu; Zhijun Huang; Bin Yi (Redox Biology)
Purpose: This research explores the consequences of being exposed to PM2.5 contribute to renal injury while also evaluating the protective role of Vitamin D-VDR signaling in alleviating mitochondrial calcium imbalance and oxidative stress in renal tubular cells. Methods: Animal models of chronic PM2.5 exposure were used to simulate environmental conditions in wild type and VDR-overexpressing mice specific to renal tubules. In parallel, HK-2 cell lines were treated with PM2.5 in vitro. Mitochondrial function, calcium concentration, and oxidative stress markers were assessed. VDR activation, achieved through genetic overexpression and paricalcitol, was induced to examine its effect on mitochondrial calcium uniporter (MCU) expression and mitochondrial calcium regulation. Results: PM2.5 exposure caused significant mitochondrial damage in renal tubular cells, including mitochondrial calcium overload, increased oxidative stress, reduced membrane potential, and diminished ATP production. Elevated MCU expressions were a key contributor to these disruptions. VDR activation effectively reversed these effects by downregulating MCU, restoring mitochondrial calcium balance, reducing oxidative stress, and improving renal function. Conclusion: This study shows that activating Vitamin D-VDR signaling shields the kidneys from PM2.5-induced damage by reestablishing mitochondrial calcium balance and lowering oxidative stress via inhibition of the MCU. These results unveil a new protective role of VDR in defending against environmental pollutants and suggest that targeting the MCU could offer a potential therapeutic strategy for treating chronic kidney disease linked to pollution exposure.